An assessment of the potential efficiency and profitability of valueaddition and marketing innovations involving smallholder farmers under a pilot system in Tanzania - Abass, A.; Abele, S.; Mlingi, N.; Rweyendela, V.; Ndunguru, G. (2009)
An assessment of four pilot processing centers in Tanzania, established for processing cassava to high quality cassava flour, chips and starch based on IITA technologies was carried out from 2003 to 2005. We followed the value chain analysis approach, looking in detail at processing efficiency and relating it to market dynamics in particular of the fresh cassava or raw material market. Locations with large volumes of fresh cassava were found to be very favorable for such enterprises, as prices are likely to be low and surplus production ensures a steady flow of fresh cassava as raw material. Locations with little available cassava are not suitable, even if prices are low, as raw material is not readily available. Sourcing fresh cassava either on-farm or in the local market during the last quarter of the year was potentially difficult and very expensive. Trade margins of fresh cassava were significantly higher in markets with obvious scarcity, but relatively low in higher volume markets. Potential profitability of the infant processing sites was remarkably influenced by capacity utilization. At 100% capacity utilization, at Chisegu, a high quality cassava flour site, profitability was US$ 1,876, NPV was US$ 6,402, and IRR was 77%. At the high quality cassava flour site in Zogowale operated at 48% capacity utilization, profitability was US$ 1,640, NPV was US$ -9,429. At Bungu, a cassava chips site, although operated at 59% capacity utilization the profitability was US$ 2,126, NPV was US$ 8,698, and IRR was 135%. When the Zogowale operations were adjusted to 100% capacity utilization, the NPV increased substantially to US$ 11,013 while IRR also increased substantially to 177%. Although starch production is the most capital intensive production technology of the three technologies studied, the starch site at Mtimbwani when operated at 100% installed capacity had total profitability of US$ 4,482, a NPV, US$ 15,958, and IRR 91 %. Other factors, including infrastructure such as road and water, cultural attitudes of smallholder processors/farmers to work and their business outlook also affected the performances of the processing enterprises.